The implementation of 5D BIM in construction management: benefits and challenges faced by construction professionals / Nur Dalisya Humaira Mohd Saupi and Noor Akmal Adillah Ismail - Mohd Saupi, Nur Dalisya Humaira; Ismail, Noor Akmal Adillah (UiTM Press, 2024)
The rapid evolution of technology necessitates integrating new tools within educational curricula, especially in fields like technical and construction education. Building Information Modelling (BIM) is one such advanced technology that has been increasingly adopted by universities worldwide to enhance Architecture, Engineering, and Construction (AEC) programs. BIM facilitates the creation of digital information models, significantly benefiting construction management through improved design comprehension, quantity take-off, and cost estimation. Among its advancements, 5 Dimensional (5D) BIM stands out by enabling users to visualise the impact of design changes on both project cost and timeline. However, its usage is still at the infancy level due to some issues. This paper examines the benefits and challenges of integrating 5D BIM into construction management within the Malaysian construction industry. Data were gathered via an online survey targeting contractors, consultants, and developers, and further analysed using SPSS Average Index (AI). Findings reveal that 5D BIM is highly valued for optimizing time management, enhancing quality control, and improving cost estimation. Nevertheless, significant challenges hinder its broader adoption, including a lack of training and expertise, integration difficulties with existing workflows, technical limitations, and lack of acceptance and standardisation of 5D BIM practice. By addressing these challenges, the construction industry in Malaysia can better harness the potential of 5D BIM, leading to enhanced project efficiency and productivity.